Utilization of air injection together with spring wire and twisted tape to enhance performance of vertical tube with downward stream. Issue 3 (14th September 2022) - Safrangian, Ali; Rostampour, Vahid; Jafarmadar, Samad; Piri, Ahmad
ABSTRACT: Present investigation, provides thermal and exergetic evaluations of downward gas–liquid two-phase flow within a vertical tube, which equipped two types of turbulators (spring wire and twisted tape). The vertical tube was put under fixed value of heat flux, which was provided via flexible wire heaters that were wrapped around the tube. The volume fraction varied between the values of 0.11 and 0.77. For each type of turbulators three different twist ratios of 2.2, 4.4, and 6.6 were considered to check the effect of twist ratio. Findings revealed that the maximum value of the Nu number, observed in the tube with Spring wire turbulator was 17% more than that in the tube with a Twisted tape turbulator. Also, it was found that the minimum value of the C.B.R factor was about 0.81 which was associated with Twisted tape that had the twist ratio of 4.4. Furthermore, the ratio between the maximum value of exergy efficiency associated with Spring wire turbulator and Twisted tape turbulator was about 1.11.